Performance evaluation of novel vibrant multi-petalous germplasms in Adenium (Adenium obesum) - Patel, G D; Singh, Alka; Shah, H. P.; Patel, V. B.; Pandey, Avnish; Kumar, Dinesh; Chavan, S. K. (Current Horticulture, 2025)
Research aiming on crop improvement has been conducted in Adenium, a popular flowering pot plant with the basic objective of novel flower morphological traits at the Advance Technology Centre of Soilless System, Department of Floriculture and Landscape Architecture, NAU, Navsari, during 2016-2021. Hybridization was done in Adenium involving six parents where in three varieties were taken as male parents, viz., Double Sweet Heart (DSH), Vithoons White (VW), Pineapple Rose (PR) and three as female parents, viz., Arrogant(A), Mor Lok Dok (MD) and Black Dragon (BD) and their crosses were studied. Among the different crosses, NAMDDSH (MD X DSH) and NAADSH (A X DSH) appeared to have novel traits with multipetalous flower form in white and deep red flower colour respectively. These crosses were further multiplied by grafting and evaluated along with their parent varieties for stability during 2019 to 2021. NAMDDSH bearing white flowers and NAADSH with red flowers were found novel and significantly superior in terms of the flower form with 10 petals, number of flowers per cluster (8-9), flowers opened at a time on a cluster (3.6-4.4) and flower longevity (11-12.5 days). Besides NAADSH exhibited enhanced flower size (8-8.16 cm) among all the germplasms. These germplasms can be further exploited for commercial application as well as for breeding.